Training-induced changes in morphological and motor parameters in female football players - Lewandowski, Andrzej; Krakowiak, Helena; Kozicka, Magdalena; Klimek, Wioleta; Piekorz, Zuzanna (Akademia Wychowania Fizycznego w Poznaniu)
Aim of Study. The aim of this study was to analyse morphological and motor changes in young elite female football players during preparatory phase of a yearly training cycle. We assumed that preparatory phase in football training causes a decrease in body fat mass, increase in body weight, particularly in muscle mass of lower limbs, as well as an improvement in motor skills, endurance and speed. Methods. The study included elite female football players from KKP MAX-Sprint Bydgoszcz team. Their basic morphological parameters, including body composition and physical performance expressed by outcomes of flexibility, static and explosive strength, speed and endurance EUROFIT battery tests, were documented at two time points: beginning and end of preparatory phase of a yearly training cycle. Data. The Shapiro-Wilk test (assessment of the distribution of variables), Student t-test (assessment of the significance of the dependent variables’ differences) and Mollison’s index (assessment of the scope of changes of the variables tested) were used. The threshold of statistical significance for all tests was set at 0.05. Results. Morphological changes were manifested mainly by an increase body weight (D = 0.78 kg, p = 0.012) including protein content (D = 0.15 kg, p = 0.005) and in body fluid volume (D = 0.33,p = 0.032) and fat-free mass, particularly in lower limbs (for the right leg D = 0.12 l, p = 0.003; for the left leg D = 0.10 l, p = 0.006). Motor changes were manifested by an improved speed agility (D = 2.79 s, p = 0.000), flexibility (D = 6.25 cm, p = 0.000), explosive strength (D = 8.67 cm, p = 0.001) and static strength (D = 3.00 kG, p = 0.016). Conclusions. A significant increase in muscle mass and speed suggests that football training exerts specific, desirable effects on morphological and motor characteristics in female players. Preparatory phase in football training does not result in unfavourable changes in morphological and motor characteristics in female players.
Keywords: competitive sports; body composition; physical fitness; preparatory phase; feminine sports